(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
The transition of traditional learning to digital learning has faced great changes, mainly during this pandemic. In the introduction part of the research, the definitions of traditional learning and online teaching and the background of the study are stated. The aim of the study is to show a comparison between student engagement in the traditional way of learning and the online learning process in the education system. The different points related to the study topic and Vygotsky’s theory has stated. The primary data collection process, descriptive method, and deductive approach of research are followed here. SPSS and ANOVA, frequency analysis, and correlation have been done here. Data those have gathered from 55 different students with 13 questions and their analysis has stated. The interpretation of data has done with SPSS. A comparison of the literature review and the relation between the results that are collected are analyzed in the discussion part. Thus, it can be concluded that the traditional learning practice created more impact for engagement of students. The online teaching process has made less engagement in compare with transitional process.